Diverging Fates of the Pacific Ocean Oxygen Minimum Zone and Its Core in a Warming World. Issue 6 (23rd November 2022) - Busecke, Julius J. M.; Resplandy, Laure; Ditkovsky, Sam J.; John, Jasmin G.
Abstract: Global ocean oxygen loss is projected to persist in the future, but Earth system models (ESMs) have not yet provided a consistent picture of how it will influence the largest oxygen minimum zone (OMZ) in the tropical Pacific. We examine the change in the Pacific OMZ volume in an ensemble of ESMs from the CMIP6 archive, considering a broad range of oxygen (O2 ) thresholds relevant to biogeochemical cycles and ecosystems (5–160 µmol/kg). Despite OMZ biases in the historical period of the simulations, the ESM ensemble projections consistently fall into three regimes across ESMs: an expansion of low oxygenated waters (+0.8 [0.6, 1.0] × 10 16 m 3 /century for O2 ≤ 120 µmol/kg, ESM median and interquartile range); a slight contraction of the OMZ core although more uncertain across ESMs (−0.1 [−0.5, 0.0] × 10 16 m 3 /century for O2 ≤ 20 µmol/kg); and at the transition from contraction to expansion regimes, a spatial redistribution but near‐zero change in the volume of hypoxic waters (0.0 [−0.3, +0.1] × 10 16 m 3 /century for O2 ≤ 60 µmol/kg). Changes in circulation and biology dictate the shift from expansion to contraction. Specifically, reduced subtropical ventilation controls the expansion of low oxygenated waters, while a combination of circulation and biological changes explains the contraction of the core (likely changes in mixing, reduced intermediate ventilation and oxygen demand). Increased model complexity (e.g., ecosystem dynamics and equatorial circulation) likely stabilize the OMZ response, suggesting that future changes might lie in the lower bound of current projections. The expansion of low oxygenated waters which delimit the optimum habitat of numerous marine species would severely impact ecosystems and ecosystem services. Plain Language Summary: Expansion of ocean areas with low oxygen concentrations threatens marine animals and could increase the production of greenhouse gases that warm the Earth. An essential question is how these low oxygen "blobs, " called oxygen minimum zones (OMZs), will evolve in the future. OMZs are difficult to simulate in climate models because they result from two strongly opposing processes: Physical supply of oxygen via the ocean circulation and oxygen consumption by biological respiration. Previous studies using older generations of models could not conclude whether the largest of these zones in the Pacific would grow or shrink in the future. We show that the Pacific OMZ will grow in response to climate change but that its core—where oxygen is lowest—will shrink. This expansion of the broad OMZ is caused by a weaker supply of oxygen rich waters by ocean circulation, whereas the contraction of the OMZ is influenced by a combination of changes in ocean circulation and biological activity. The expansion of the outer OMZ is likely bad news for the marine species that suffer in low oxygen conditions, and the people that depend on them (fishing and tourism). Key Points: The Pacific oxygen minimum zone (OMZ) will expand but its core might contract under sustained anthropogenic forcing Non‐thermal changes (ocean circulation and biology) dictate the shift from core contraction to OMZ expansion The OMZ expansion would compress the habitat of marine species and impact ecosystems and ecosystem services